Evaluation of the effectiveness and safety of icariin in the treatment of knee osteoarthritis: A protocol for a systematic review and meta-analysis. Issue 50 (17th December 2021) - Liu, Lang; Zhao, Changwei; Zhao, Shuang; Xu, Hanxun; Peng, Zeyu; Zhang, Binghua; Cai, Wenjun; Mo, Yifang; Zhao, Wenhai
Abstract: Background: Knee osteoarthritis (KOA) is a chronic degenerative disease involving cartilage and surrounding tissues. It causes a huge burden to social and medical resources and seriously affects people's living and working ability. In recent years, people have become increasingly interested in the application of Chinese medicine monomers to treat KOA. Among them, icariin plays an important role in the clinical treatment of KOA. Therefore, to evaluate the effectiveness and safety of icariin in the treatment of KOA, we conducted this study to provide a new basis for the clinical treatment of KOA. Methods: We propose a systematic search of the PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure, Wanfang, and China Biomedical databases for all randomized controlled trials examining the use of icariin in the treatment of KOA patients up to October 20, 2021. The screening and data extraction processes will be performed independently by 2 researchers. We will use the Cochrane risk bias assessment tool to evaluate the quality of the studies that met the inclusion criteria. The data will be statistically analyzed using RevMan5.3 software. Result: This study will provide high-quality evidence for the effectiveness and safety of icariin in the treatment of KOA. Conclusion: The purpose of this study was to explore the efficacy of icariin in the treatment of KOA and to provide clinicians and patients with new treatment strategies. INPLASY registration number: INPLASY2021110015.